Flexible four-port MIMO antenna for 5G NR-FR2 tri-band mmWave application with SAR analysis - Manish Sharma; Bhaskara Rao Perli; Lovish Matta; Tathababu Addepalli; Kanhaiya Sharma; Fadi N. Sibai (Scientific Reports)
Abstract This paper introduces a compact, triband four-port Multiple Input Multiple Output (MIMO) antenna optimized for mmWave 5G and navigation services. The antenna is built on a Rogers RT Duroid 5880 substrate, with dimensions of 31 × 42 mm² and a thickness of 0.4 mm. It utilizes a 50 Ω microstrip line to feed a stub-type radiating patch, creating a dipole-loop type structure on the substrate’s top side, with a full ground plane for narrowband. The antenna is initially designed for 38 GHz but was subsequently modified for triband performance by tapering the edges of the stub shape, enabling it to function across multiple frequency ranges. The tapered edges of the radiating patch enhance resonance across the three bands. To improve isolation and bandwidth, a parasitic element is strategically placed between the MIMO elements, results isolation greater than 30 dB at the 32 GHz and 38 GHz bands. The MIMO elements are mirror images placed adjacent to one another, while the other two elements are arranged 180º apart, ensuring compactness. The proposed antenna operates across three frequency bands: 27.76–28.15 GHz (n261), 32.02–32.46 GHz (part of n260 and n261), and 37.39–38.586 GHz (part of n260), offering enhanced resonance and improved isolation. The parasitic element reduces mutual coupling between adjacent elements, improving diversity parameters such as Envelope Correlation Coefficient (ECC) < 0.0010, Diversity Gain (DG) = 10 dB, Channel Capacity Loss (CCL) = 0.15 bits/sec/Hz, Total Active Reflection Coefficient (TARC) < -10 dB, and Mean Effective Gain (MEG) between − 3 and − 12 dB across all ports. Specific Absorption Rate (SAR) analysis for on-body applications confirms safe levels, with values below 1.6 W/kg at the resonating frequencies. Bending tests also show favourable results within the application bandwidth, further validating the antenna’s robustness. These technical improvements make the antenna highly suitable for integration into smart devices, defence navigation systems, mobile phones, and future 5G applications.